Sikap dan Dukungan Keluarga dalam Merawat Pasien Orang dengan Gangguan Jiwa (ODGJ) di Wilayah Kerja Puskesmas Patia Kabupaten Pandeglang Tahun 2023 - Sukiyah, Dodon; Suratmi, Tri; Indrawati, Lili (LPPM Universitas Respati Indonesia, 2023)
Patients with mental disorders (ODGJ) require special treatment. In the treatment process, family involvement is expected. This research aims to study and explain the attitudes and support of families in caring for ODGJ in the working area of the Patia Health Center, Pandeglang district. This research uses a quantitative approach with a cross sectional design. The population in this study was 126 patients with mental disorders with a sample of 56 respondents who were families who provided care for ODGJ patients using accidental sampling data collection techniques. The research instrument is a questionnaire which was constructed by the researcher himself and has been tested for validity and reliability using a trial sample of 20 people. Based on the results of the analysis using chi square statistical testing, it was found that the p-value of family support (0.018), family role (0.024) and source of family support (0.001) was related to the length of treatment for ODGJ. The dominant variable related to the length of treatment for ODGJ is family support (0.031) with an OR value of 11.7. Family support has an 11.7 times chance of helping the healing process. Keywords : Attitudes, Family Support, Care